A society sensation - Valentino, Rudolph, 1895-1926; Myers, Carmel, 1899-1980; Sheehan, Perley Poore, 1875-1943 (Academic Video Online, 2007)
This silent film drama, directed by Paul Powell, features Carmel Myers, Rudolph Valentino, and Lydia Yeamans Titus.